2015
DOI: 10.1007/s10950-015-9485-0
|View full text |Cite
|
Sign up to set email alerts
|

A more accurate relocation of the 2013 M s7.0 Lushan, Sichuan, China, earthquake sequence, and the seismogenic structure analysis

Abstract: A more accurate relocation of the 2013 M s 7.0 Lushan, Sichuan, China, earthquake sequence, and the seismogenic structure analysis Abstract We use a combined earthquake location technique to relocate the M s 7.0 Lushan, Sichuan, China, earthquake sequence of April 20, 2013. A stepwise approach, employing three existing location methods (the HYPOINVERSE method, the Minimum 1-D model, and the Double Difference method), is used to improve location precision by iteratively revising the velocity model station corre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
26
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 30 publications
(29 citation statements)
references
References 26 publications
(41 reference statements)
3
26
0
Order By: Relevance
“…In order to reveal how seismicity evolved in the strike‐perpendicular direction, especially the activation of a back thrust fault [ Han et al , ; Fang et al , ; Long et al , ], we project all detected events along the strike‐perpendicular direction of 140°clockwise relative to north (Figure ). Similar to the along‐strike profile, we observe an expansion of aftershocks in the normal‐to‐fault direction for both standard (Figure b) and relocated catalogs (Figure d).…”
Section: Resultssupporting
confidence: 80%
See 2 more Smart Citations
“…In order to reveal how seismicity evolved in the strike‐perpendicular direction, especially the activation of a back thrust fault [ Han et al , ; Fang et al , ; Long et al , ], we project all detected events along the strike‐perpendicular direction of 140°clockwise relative to north (Figure ). Similar to the along‐strike profile, we observe an expansion of aftershocks in the normal‐to‐fault direction for both standard (Figure b) and relocated catalogs (Figure d).…”
Section: Resultssupporting
confidence: 80%
“…To further examine spatiotemporal evolutions of early aftershocks, we project all detections along the LMS fault strike (50° clockwise from north) and center around the main shock epicenter (102.9824°N, 30.2821°E, depth 14.8 km) as listed in the relocated catalog [ Long et al , ]. As shown in Figure b for the standard catalog, seismicity expands from −15 to 5 km along‐strike relative to the main shock in the first 1000 s to −30 to 20 km along‐strike at the end of detection period.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…However, the fine-scale fault geometry was not well imaged in the previous studies. For example, the y-shaped fault system and sharp fault planes have been shown vaguely in Han et al (2014) and Long et al (2015) and are not revealed in Lü et al (2013) and Zhang and Lei (2013). This may be due to the different datasets and earthquake location methods they used, because most of them used only several days' aftershock data recorded by the permanent seismic stations.…”
Section: Discussionmentioning
confidence: 99%
“…Some researchers conducted earthquake relocation, shearwave splitting, and earthquake tomography after the Lushan earthquake (Fang, Wu, Wang, Lü, et al, 2013;Jiang et al, 2013;Zhang and Lei, 2013;Zeng et al, 2013;Lei et al, 2014;Pei et al, 2014;Long et al, 2015). These results, together with the focal mechanism Zeng et al, 2013;Han et al, 2014) and rupture process of the mainshock (C. L. Wang et al, 2013;C.…”
Section: Introductionmentioning
confidence: 99%